Engineered endolysin of Klebsiella pneumoniae phage is a potent and broad-spectrum bactericidal agent against “ESKAPEE” pathogens - Chen, Wei; Han, Li-Mei; Chen, Xiu-Zhen; Yi, Peng-Cheng; Li, Hui; Ren, Yun-Yao; Gao, Jing-Han; Zhang, Cai-Yun; Huang, Jing; Wang, Wei-Xiao; Hu, Zhi-Liang; Hu, Chun-Mei (Frontiers in Microbiology, 2024)
The rise of antimicrobial resistance in ESKAPEE pathogens poses significant clinical challenges, especially in polymicrobial infections. Bacteriophage-derived endolysins offer promise in combating this crisis, but face practical hurdles. Our study focuses on engineering endolysins from a Klebsiella pneumoniae phage, fusing them with ApoE23 and COG133 peptides. We assessed the resulting chimeric proteins’ bactericidal activity against ESKAPEE pathogens in vitro. ApoE23-Kp84B (CHU-1) reduced over 3 log units of CFU for A. baumannii, E. faecalis, K. pneumoniae within 1 h, while COG133-Kp84B (CHU-2) showed significant efficacy against S. aureus. COG133-L1-Kp84B, with a GS linker insertion in CHU-2, exhibited outstanding bactericidal activity against E. cloacae and P. aeruginosa. Scanning electron microscopy revealed alterations in bacterial morphology after treatment with engineered endolysins. Notably, CHU-1 demonstrated promising anti-biofilm and anti-persister cell activity against A. baumannii and E. faecalis but had limited efficacy in a bacteremia mouse model of their coinfection. Our findings advance the field of endolysin engineering, facilitating the customization of these proteins to target specific bacterial pathogens. This approach holds promise for the development of personalized therapies tailored to combat ESKAPEE infections effectively.